Être femme de lettres au Brésil à l’époque impériale (1822-1889) : le statut social d’une « minorité » porteuse d’une voix dissonante dans l’espace public - Sébastien Rozeaux (Centre de Recherches sur les Mondes Américains, 2014)
This article focuses on the reconstruction of a representative sample of the literary milieu as it gradually emerged nineteenth-century Brazil. This literary milieu looks like a narrow social group, predominantly male, reflecting the structures of an imperial society deeply influenced by Roman law that submits women to male authority, whether that of the father or husband. Deprived of civil rights, denied access to higher education, women of the upper class remained confined to domestic and ornamental roles that deterred them from pursuing a literary career and spared them the need to work for a living. However, a handful of women made their way through the literary world; through the study of the social trajectories and discourses of these few women of letters, I would like to propose a new perspective on the situation of women in the Brazilian literary field and in a patriarchal, Catholic and slave society. Although it is premature to talk about a "feminist" discourse, this article is an opportunity to measure how these women helped to impose a voice of their own in the public space, and promote a new status for women in society, especially in literary circles, in the second half of the XIXth century.